Indian farmers’ welfare: Indian farmers’ welfare: Policies, approaches, strategies and prophecy - Dastagir, M B; Naga Sindhuja, P V; Arun V, Sai; Singh, Addamay (Indian Farming, 2022)
The study shows that if farmers are empowered, the nation would become self-sufficient. This study also revealed the highest percentage share of India’s land use to the world was under land area equipped for irrigation, arable land and crop land. The study found that most of the farmers belong to marginal and small categories in India. Uttar Pradesh, Bihar, Maharashtra, Madhya Pradeshand Karnataka have the highest number of operational holders in India. The number of small size operational holdings has increased,while medium and large size operational holdings have gone down within the 5 years due to fragmentation of land. PMFBY, Soilhealth card scheme, PMKSY, eNAM, FPO, RKVY, SMAM, MSP, PM-AASHA, and PM-Kisan are the currently existing policy programsimplemented by India to increase the farmers’ welfare. Price approach and income approach are the two important approaches to improve farmers’ welfare. Market transparency, market centric policies, basic infrastructure facilities, transfer of agricultural knowledge to farmers, off-farm employment, favourable insurance programs, and delivery of basic services are the main strategiesto improve the farmers’ welfare. The study strongly suggests implementing the price insurance and price loss program as well as direct income approach.